El impacto de la ortografía en la pronunciación española de los estudiantes húngaros: un estudio empírico - Brdar, Teréz Mirjam; Baditzné Pálvölgyi, Kata; Gaál, Zoltán Kristóf (Verbum – Analecta Neolatina, 2024)
The aim of this paper is to discover whether orthography has an impact on the Spanish interlanguage pronunciation of learners of Spanish with Hungarian L1. Eight Spanish graphemes were selected, and the oral productions of 20 university students were analysed using the acoustic software Praat and compared with the productions of two native speakers of Spanish and one native speaker of Hungarian. It was assumed that orthography-based negative transfer would be observed in the cases in which the grapheme-phoneme correspondences between the L1 and the L2 lack complete transparency. The pronunciation of the following graphemes was included in the study: c before a low vowel, before a consonant and before a mid vowel, ch, g before a high vowel, h, ll, v and z. The results corroborate the main hypothesis: negative transparency phenomena based on orthography can be observed in the case of the graphemes h, v, z and g preceding a high vowel, in the cases of which the transparency between Spanish and Hungarian grapheme–phoneme correspondences is not complete.